Lessons Learned from the World Bank’s Accounting and Auditing ROSC Program - Hegarty, John (World Bank, Washington, DC, 2013)
This paper addresses challenges to the successful implementation of international accounting and auditing standards which have been observed by the World Bank when carrying out the Report on the Observance of Standards and Codes (ROSC) accounting and auditing assessments. It describes the ROSC program, outlines the methodological approach followed, identifies problems common across several jurisdictions, and makes suggestions for initiatives that could enhance the implementation of international standards. The ROSC results show that governments have primarily concentrated on adopting legislation mandating or allowing the use of international standards, and the private sector has sought to increase the competence of individuals and firms to apply international standards. This paper provides an overview of the main program of Bank diagnostic work in the field of private sector financial reporting: (ROSC) It summarizes some of the main findings of the 38 assessments that have been carried out to date, with specific reference to the challenges to the successful implementation of international accounting and auditing standards. Attention is drawn to the need for international consensus on a comprehensive framework of principles for the regulation of accounting and auditing that also addresses issues of implementation, which is not covered by existing international accounting and auditing standards. The paper concludes by raising a number of other issues to be discussed and resolved going forward, if countries are to receive the support they need to successfully implement international standards and reap their full benefits.